Tissue-engineered vascular grafts and regeneration mechanisms. (April 2022) - Wei, Yongzhen; Wang, Fei; Guo, Zhikun; Zhao, Qiang
Abstract: Cardiovascular diseases (CVDs) are life-threatening diseases with high morbidity and mortality worldwide. Vascular bypass surgery is still the ultimate strategy for CVD treatment. Autografts are the gold standard for graft transplantation, but insufficient sources limit their widespread application. Therefore, alternative tissue engineered vascular grafts (TEVGs) are urgently needed. In this review, we summarize the major strategies for the preparation of vascular grafts, as well as the factors affecting their patency and tissue regeneration. Finally, the underlying mechanisms of vascular regeneration that are mediated by host cells are discussed. Graphical abstract: Unlabelled Image Highlights: Tissue engineered vascular grafts (TEVGs) are urgently needed in the clinic for the treatment of cardiovascular diseases. Different strategies have been developed to fabricate TEVGs with optimized physical, chemical and biological performance. Recipient endogenous stem/progenitor cells (SPCs) plays a vital role in the regeneration of TEVGs.